The Brief History of Entrepreneurial Education - Hägg, Gustav; Kurczewska, Agnieszka (Entrepreneurship Education, 2022)
This chapter presents a brief history of the field with a focus on the socio-economic background of the rise of entrepreneurial education and its path towards academic legitimization. The aim is to interpret and discuss the characteristics and evolution of entrepreneurial education research. Therefore, we examine the unique close link between the socio-economic reality and an academic agenda from both historical and research perspectives. We discuss different factors that enabled entrepreneurial education to experience such exponential growth on a global scale. Our discussion provides a basic understanding of the field of entrepreneurial education and its evolution. This chapter presents a brief history of the field with a focus on the socio-economic background of the rise of entrepreneurial education and its path towards academic legitimization. The aim is to interpret and discuss the characteristics and evolution of entrepreneurial education research. A historical contextualization of the birth and rise of entrepreneurial education is important, as its profile and development have been shaped by context, both within academia and by external views on its importance for societal development. Entrepreneurial education was initially positioned in the business area, which meant that mainly business school students or those studying management/business administration were exposed to it. At that stage, entrepreneurship was regarded as a higher education subject and was only offered to lower education levels as part of vocational training. The fields of entrepreneurship and entrepreneurial education developed in parallel, with entrepreneurship ahead but also struggling in terms of a conceptual and methodological debate.